Strategies for the effective use and development of mineral rights belonging to indigenous peoples in South Africa - Rungan, Sivalingum Venigiaum (My University, 2013)
At the commencement of this research, South Africa(SA) had been twelve years into democracy and two years after the Mineral and Petroleum Resources Development Act (MPRDA) and Broad-Based Socio-Economic Empowerment Charter for the South African Mining Industry (Mining Charter) became effective. As a result, the mining industry is undergoing a transformation to redress the imbalances of the past and to enable greater participation of Historically Disadvantaged Persons in the industry. While the issues affecting Indigenous Peoples (IPs) may have become clouded by Black Economic Empowerment and transformation, IPs have begun to assert their rights. This is particularly so with regard to the exploitation of the minerals on their land to enable them effectively use and develop such minerals to secure their own development. This research, accordingly, seeks to answer the fundamental question of whether IPs in SA could exploit minerals and play a meaningful role in their own socio-economic development. The three parties (mining companies, IPs and government) to a mining transaction of would need to work together to ensure that IPs are able to effectively benefit from such mineral exploitation. Although IPs are in a significantly weaker position as compared to governments and companies, it does not obviate the responsibility of IPs to be proactive in their own development. In considering an appropriate definition of IPs in SA, the legal development of the segregation of IPs from mining to loss of land, various case studies and toolkits, fundamental strategic (“DRESTALL”) and general principles lead to appropriate strategies being developed that can be used for IPs to effectively use and develop their mineral rights. However, in adopting the relevant strategies, it should be noted that a long-term vision must be adopted by IPs.